Pengaruh Konformitas dan Literasi Keuangan terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi FKIP UNS - Fattah Sabillah; Aniek Hindrayani; Khresna Bayu Sangka (Departement of Mathematics Education, 2024)
The aim of this research is to identify the influence of conformity and financial literacy on the consumer behavior of FKIP UNS Economics Education students. The research method used is quantitative with a population of Economic Education students class 2019-2021. The sampling technique applies the Proportional Random Sampling technique with a sample size of 168 respondents. Data collection was carried out using a questionnaire. Data analysis uses simple regression analysis, simultaneous regression test (f test), partial regression test (t test), and analysis of the coefficient of determination. The results of the research are (1) there is a positive influence between the conformity variable and the consumptive behavior of FKIP UNS Economics Education students with a calculated t value of 9,713 > t table 1,65414. The significance value in the F test is 0,000 (< 0,05), (2) there is a negative influence between the financial literacy variable and the consumptive behavior of FKIP UNS Economic Education students with a calculated t value of 5,661 and t table 1,65414 and a significance value of 0,000 (> 0,05). (3) There is a positive influence between the conformity and financial literacy variables on the consumer behavior of FKIP UNS Economics Education students with an F table value of 3,05 < F count 36,864. The significance value in the F test is 0,000 (< 0,05).